Initial levetiracetam versus valproate monotherapy in antiseizure medicine (ASM)-naïve pediatric patients with idiopathic generalized epilepsy with tonic-clonic seizures. (October 2021) - Abdelmesih, Sherry Kodsy; Elkhateeb, Nour; Zakaria, Mostafa; Girgis, Marian Y.
Highlights: Valproate and levetiracetam are effective as monotherapy in antiseizure medicine (ASM)-naïve pediatric patients. Both ASMs are effective as monotherapy in patients with febrile seizure plus. Both ASMs have a similar favorable efficacy across different pediatric ages. Levetiracetam remains well tolerated at higher doses than valproate. Abstract: Introduction: Levetiracetam (LEV) is a second-generation antiseizure medicine (ASM) with broad-spectrum efficacy and tolerability. Few studies have compared the efficacy of valproate (VPA) and LEV as monotherapy in the pediatric population. Herein, we compare the efficacy, tolerability and safety of LEV monotherapy with those of VPA monotherapy in ASM-naïve pediatric patients with idiopathic generalized epilepsy with tonic-clonic (GTC) seizures. Methods: We retrospectively analyzed the clinical and electroencephalographic (EEG) data of these ASM-naïve pediatric patients who were treated with either oral VPA or oral LEV as monotherapy for over 2 years at our center. Results: This study included 60 patients with a seizure onset age between 2 months and 12 years. The patients on VPA (29 patients) and LEV monotherapy (31 patients) showed similar favorable 6-month treatment outcomes (complete seizure control in 79.31% vs 80.64%, p = 0.468052). Age at epilepsy onset, epilepsy syndrome, EEG features and ASM dose were not significant predictors of the 6-month treatment outcomes in either group. Lower seizure frequency at presentation was a predictor of favorable 6-month treatment outcomes in the LEV group but not in the VPA group. VPA and LEV treatment showed similar favorable 6-month treatment outcomes in the febrile seizures plus and patients with unidentified epilepsy syndrome subgroups. None of the patients discontinued VPA or LEV due to treatment-associated adverse effects. Discussion: Our study showed that compared to VPA monotherapy, LEV monotherapy in ASM-naïve infants and children with idiopathic generalized epilepsy with GTC seizures has a similarly favorable efficacy and tolerability, independent of age, EEG features and epilepsy syndrome. Graphical abstract: Image, graphical abstract